Geant4 simulation results for the designed UGET-v1 tomographic measurement device - Jansson, Peter (Uppsala University, 2017)
Results from simulations performed with Geant4 for the UGET v1 of a tomographic measurement device, designed in the UGET project.

See "PNNL-25995 A Viability Study of Gamma Emission Tomography for Spent Fuel Verification: JNT 1955 Phase I Technical Report" by Smith et al (2016) for detailed information.

The dataset was originally published in DiVA and moved to SND in 2024.

Resultat av simuleringar genomförda med Geant4 för UGET v1 av ett tomografisk mätinstrument designat i UGET projektet.

Se "PNNL-25995 A Viability Study of Gamma Emission Tomography for Spent Fuel Verification: JNT 1955 Phase I Technical Report" av Smith et al (2016) för detaljerad information.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Geant4 simulation results for the designed UGET-v1 tomographic measurement device
Keywords: nuclear fuels; kärnbränslen; Tomography; Tomography; Geant4; Geant4; Nuclear fuel; Nuclear fuel; Physics with specialization in Applied Nuclear Physics; Physics with specialization in Applied Nuclear Physics; Simulation results; Simulation results; Safeguards; Safeguards; Subatomic Physics; Subatomär fysik